Simulating and validating an ideal factory at Volvo Cars Corporation - Bergentz, Anton; Blum, Mikael (My University, 2020)
A dynamic market with fast paced changes and shifting customer demands requires companies to adjust and find new ways to improve their production facilities in order to stay competitive. A critical industry is the automotive industry where customers order highly customized products with short delivery times as an expectation. This has led to an increased use of concepts such as Industry 4.0 to improve the production and the utilization of resources. Furthermore, digital tools, such as flow simulation models, has become more and more popular to determine how improvements could affect the production facilities without having to implement them in the real system. With that said, this thesis investigates some of the possibilities with the use of digital models, and how to create a credible model of a facility that does not yet have a physical counterpart. The project started with the creation of a simulation model of an assembly flow in collaboration with an automotive industry. Simultaneously as it was built, the model was verified and validated with some of the already existing techniques to investigate if a credible model could be achieved despite not having any physical counterpart to compare with. The results indicated that it was possible to build a credible model in accordance to the intended purpose, but where this is more thoroughly discussed in the report. Further, experiments were performed when the model had been created to investigate the appropriate buffer sizes and fixtures needed to increase the performance and cost efficiency of the system. The main conclusions from the project are that the communication with experts and the end-user grows and becomes the most important source of information when verifying and validating a system with no physical counterpart. Also, putting time into the problem formulation phase and formulating the purpose of the model together with the end-user is of greatest importance to achieve a credible model.
Keywords: Discrete Event Simulation, Validation, Verification, Automotive